Communications technology guidelines for EMS - Marihart, D.J (IEEE Transactions on power delivery)
The purpose of this Guideline Technical Paper is to provide a summary of the different communications technologies available for use or application with EMS/SCADA system projects. All of the various communication media are addressed with a brief description along with tables of the advantages and disadvantages of each and recommendations for choosing the most appropriate communication technology. The technologies discussed are: twisted pair metallic cable; coaxial metallic cable; fiber optic cable (either optical power ground wire (OPGW), all dielectric self supporting (ADSS), or wrapped types (WOC)); distribution line carrier (DLC); power line carrier (PLC); satellite (VSAT, LEO, others); leased service; VHF radio (mobile); point-to-point UHF radio; multiple address radio system (MARS) 400/900 MHz UHF radio; trunked mobile UHF radio; spread spectrum UHF radio (monitor frequency for potential interference before installation); and microwave radio (2-40 GHz)